Instrumentation in process control - Wightman, E. J. (International scientific series (Butterworths (Firm)), 1972)
Instrumentation in Process Control details the elements of transducers utilized in doing various measurements. The book also deals with the problems in data gathering from physical processes. The text also examines the different schemes of relaying or showing the data and compares the many ways by which data could be processed. The first chapter opens with an introduction to the study; it then proceeds to talk about primary measurements and notes the importance of selecting the transducer, having precision in measurements, and having a properly designed system. This chapter also presents vario.